Chronotherapeutics for Solid Tumors - Claire O. Kisamore; Brittany D. Elliott; A. Courtney DeVries; Randy J. Nelson; William H. Walker (MDPI AG, 2023)
Circadian rhythms are internal manifestations of the 24-h solar day that allow for synchronization of biological and behavioral processes to the external solar day. This precise regulation of physiology and behavior improves adaptive function and survival. Chronotherapy takes advantage of circadian rhythms in physiological processes to optimize the timing of drug administration to achieve maximal therapeutic efficacy and minimize negative side effects. Chronotherapy for cancer treatment was first demonstrated to be beneficial more than five decades ago and has favorable effects across diverse cancer types. However, implementation of chronotherapy in clinic remains limited. The present review examines the evidence for chronotherapeutic treatment for solid tumors. Specifically, studies examining chrono-chemotherapy, chrono-radiotherapy, and alternative chronotherapeutics (e.g., hormone therapy, TKIs, antiangiogenic therapy, immunotherapy) are discussed. In addition, we propose areas of needed research and identify challenges in the field that remain to be addressed.